Analysis of Legal Aspects of The Murabahah Agreement In Islamic Banking - Choiriyah, Choiriyah; Noviani, Dwi; Saprida, Saprida (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
Islamic Banking According to Law Number 21 of 2008 concerning Islamic Banking, specifically Article 1 number 7, Islamic Banks are banks that carry out their business activities based on Islamic principles and by their nature, consisting of Islamic Commercial Banks and Islamic Commercial Banks. Islamic People's Financing. In general, Islamic banks are banks whose operational activities are based on Islamic law, or banks that base their operational activities on interpreting the Qur'an and Hadith as the basis for Islamic law. It is stated that according to Law Number 21 of 2008 concerning Islamic Banking, in Article 1 number 12, the basis of Islamic faith for bank operations is a fatwa issued by an institution authorized to issue fatwas in the field of Islamic banking. The National Sharia Council confirms that murabahah sales and purchase transactions, whether in cash or installments, with the terms and conditions being met, are financed under a murabahah contract at a Sharia bank in terms of determining profits by Sharia principles. In the Islamic banking system, there is always a need for collateral or a loan prepared with the understanding that every debtor must adhere to Islamic law, as previously explained to parents. Islamic banking allows customers to be more cooperative when purchasing goods on credit or cash.